2020
DOI: 10.1016/j.nano.2019.102084
|View full text |Cite
|
Sign up to set email alerts
|

RGD-functionalized magnetosomes are efficient tumor radioenhancers for X-rays and protons

Abstract: Rationale Radiation therapy is widely used for cancer treatment but its efficacy is limited by radioresistance and by damages caused to adjacent normal tissues. Active research aims at maximizing tumor eradication while reducing side-effects with theranostic nanoparticles that act as radioenhancers in situ. Ferromagnetic materials have been identified as promising nanotools for image-guided radiotherapy. Here, we investigated the potential of RGD-tagged magnetosomes (magnetosomes@RGD), bacterial biogenic magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…In the widely studied alphaproteobacterium Magnetospirillum gryphiswaldense each step is highly regulated by a set of more than 30 genes leading to the formation of single crystalline magnetite particles with defined size, shape and magnetic properties, which are so far unmatched by magnetic nanoparticles produced by chemical synthesis [ 4 7 ]. Hence, magnetosomes are of great potential in the biomedical and biotechnological field, and isolated magnetosomes were already successfully applied for cancer treatment, such as magnetic hyperthermia [ 8 10 ], phototherapy [ 11 ] and radiosensitization [ 12 ], as contrast agent for magnetic imaging [ 13 16 ] and as a tool in immune assays [ 17 ]. Furthermore, the proteinaceous membrane of magnetosomes from M. gryphiswaldense and related organisms can be functionalized by genetic or chemical coupling of additional functional moieties, such as enzymes for immobilization of enzymatic cascades [ 18 21 ], fluorophores, antibodies for diagnostic purposes e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the widely studied alphaproteobacterium Magnetospirillum gryphiswaldense each step is highly regulated by a set of more than 30 genes leading to the formation of single crystalline magnetite particles with defined size, shape and magnetic properties, which are so far unmatched by magnetic nanoparticles produced by chemical synthesis [ 4 7 ]. Hence, magnetosomes are of great potential in the biomedical and biotechnological field, and isolated magnetosomes were already successfully applied for cancer treatment, such as magnetic hyperthermia [ 8 10 ], phototherapy [ 11 ] and radiosensitization [ 12 ], as contrast agent for magnetic imaging [ 13 16 ] and as a tool in immune assays [ 17 ]. Furthermore, the proteinaceous membrane of magnetosomes from M. gryphiswaldense and related organisms can be functionalized by genetic or chemical coupling of additional functional moieties, such as enzymes for immobilization of enzymatic cascades [ 18 21 ], fluorophores, antibodies for diagnostic purposes e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Four plasmid constructions were built by insertion of either arsR1 or arsR= and their respective promoters followed by two different reporter genes. The gene encoding the fluorescent protein Venus was first chosen because of its small size and because it was known to be functional in MTB (33)(34)(35). However, preliminary experiments performed to measure the fluorescent signal in rich growth media, such as the one used for MSR-1, revealed a high background noise and determined that it would require additional washing to remove growth medium in order to obtain an optimal measurement.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the study showed that the RGDmagnetosomes were able to boost the efficacy of radiotherapy to a much larger extent than native magnetosomes and that the combination of the NPs and proton therapy exceeded the efficacy of X-rays at equivalent doses while increasing secondary emission after irradiation of the magnetosomes with protons versus photons. Consequently, the results indicated the therapeutic adv antages of using functionalized magnetosomes to sensitize tumors to both X-rays and protons compared to chemically-produced NPs [106].…”
Section: Bacteria-derived Nanotechnologiesmentioning
confidence: 99%